История как роман: Андрич, Селимович, Кржела, Црнянский / П. Н. Рудяков - Рудяков П. Н. (Наукова думка, 1993)
Экземпляры: КХ (19970619) / Инвентарный номер: 1019018 / Цена: 300.00 / Сис.шифр: 83.3(3/8) / Авт.знак: Р 83 / ГРНТИ: 17 / ББК: 83.3(4Ю)